Adult Spinal Deformity Patients Recall Fewer Than 50% of the Risks Discussed in the Informed Consent Process Preoperatively and the Recall Rate Worsens Significantly in the Postoperative Period. Issue 14 (15th July 2015) - Saigal, Rajiv; Clark, Aaron J.; Scheer, Justin K.; Smith, Justin S.; Bess, Shay; Mummaneni, Praveen V.; McCarthy, Ian M.; Hart, Robert A.; Kebaish, Khaled M.; Klineberg, Eric O.; Deviren, Vedat; Schwab, Frank; et al.
<x xml:space="preserve">Abstract</x> Study Design. Recall of the informed consent process in patients undergoing adult spinal deformity surgery and their family members was investigated prospectively. Objective. To quantify the percentage recall of the most common complications discussed during the informed consent process in adult spinal deformity surgery, assess for differences between patients and family members, and correlate with mental status. Summary of Background Data. Given high rates of complications in adult spinal deformity surgery, it is critical to shared decision making that patients are adequately informed about risks and are able to recall preoperative discussion of possible complications to mitigate medical legal risk. Methods. Patients undergoing adult spinal deformity surgery underwent an augmented informed consent process involving both verbal and video explanations. Recall of the 11 most common complications was scored. Mental status was assessed with the mini-mental status examination-brief version. Patients subjectively scored the informed consent process and video. After surgery, the recall test and mini-mental status examination-brief version were readministered at 5 additional time points: hospital discharge, 6 to 8 weeks, 3 months, 6 months, and 1 year postoperatively. Family members were assessed at the first 3 time points for comparison. Results. Fifty-six patients enrolled. Despite ranking the consent process as important (median overall score: 10/10; video score: 9/10), median patient recall was only 45% immediately after discussion and video re-enforcement and subsequently declined to 18% at 6 to 8 weeks and 1 year postoperatively. Median family recall trended higher at 55% immediately and 36% at 6 to 8 weeks postoperatively. The perception of the severity of complications significantly differs between patient and surgeon. Mental status scores showed a transient, significant decrease from preoperation to discharge but were significantly higher at 1 year. Conclusion. Despite being well-informed in an optimized informed consent process, patients cannot recall most surgical risks discussed and recall declines over time. Significant progress remains to improve informed consent retention. Level of Evidence: 3